The Development of E-Commerce in Indonesia Reviewed from a Digital Economy Perspective - Eva Nurazizah; Muhammad Zidan Andriawan; Gama Pratama (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2026)
This research aims to explore the development of e-commerce in Indonesia. The research was conducted with a qualitative approach, using literature studies as a source of information about the development of e-commerce, both from books and scientific articles. Advances in information and communication technology in the era of globalization have brought significant changes in various areas of life, including the trade sector. One of the tangible manifestations of this change is the presence of electronic commerce (e-commerce), which allows buying and selling transactions to be carried out digitally via the internet. Based on the discussions that have been carried out, it can be concluded that the development of e-commerce in Indonesia is taking place very quickly, especially since the COVID-19 pandemic. This growth is triggered by the high adoption of digital technology, the increase in the number of internet users, and the increasing trend of online shopping which is increasingly accepted by the public